A kind of permeable brick and its preparation method
By using copper tailings of different particle sizes and specific binders in the preparation of permeable bricks, the problems of low utilization rate and poor performance of existing permeable bricks are solved, and efficient solid waste resource utilization and performance improvement are achieved.
Patent Information
- Application Number
- CN202311618621.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-29
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-11-29
AI Technical Summary
The existing preparation methods for permeable bricks have problems such as low utilization rate of copper tailings, poor water permeability and mechanical properties.
Copper tailings with a particle size of 5-10 and copper tailings with a particle size of less than 200 are used in combination, combined with PVA aqueous solution and magnesium clay as binders, and permeable bricks are prepared through the sintering process, so that the copper tailings fine material is bonded and coated on the surface of the coarse material, forming connected pores and improving water permeability.
It improves the utilization rate of copper tailings, realizes the resource utilization of solid waste, enhances the mechanical properties and water permeability of permeable bricks, and has high pressure resistance, flexural strength and high water permeability coefficient.
Smart Images

Figure CN117567170B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic non-metallic materials, and in particular to a permeable brick and a preparation method thereof. Background Art
[0002] With the development of urbanization, my country's cities have prominent problems such as high flood discharge pressure, frequent waterlogging disasters, and serious loss of rainwater resources; urban groundwater levels have dropped, urban waterlogging, and urban heat island phenomena are serious, and the natural ecology of cities is facing a serious imbalance. For this reason, my country has proposed the concept of building a "sponge city" with the aim of improving the hydrological ecological environment of urban roads and improving the breathing function of the urban environment. Sintered permeable bricks have the characteristics of high strength and good permeability. They can effectively solve the problem of permeability of hardened roads and are one of the important materials for improving the urban ecological environment.
[0003] Copper tailings, also known as copper tailings, are composed of fine powder sand particles left after copper ore is crushed and selected. Copper ore reserves in my country are large and widely distributed. A large amount of copper tailings slag will be produced during the mining and smelting process of copper ore. The accumulation of copper tailings slag pollutes the environment and occupies land. Copper tailings contain high levels of silicon, aluminum, iron and calcium oxides, which are similar to the composition of ceramic raw material clay. Using copper tailings to prepare permeable bricks can not only fully utilize solid waste resources, but also bring good economic benefits to society.
[0004] The existing permeable brick preparation method mainly adopts the pore-forming agent method, which uses various mineral powders as the main raw materials, adds appropriate amounts of pore-forming agents and other substances, and is prepared through pressing, molding and high-temperature sintering processes. The prepared permeable bricks have high mechanical properties, but poor water permeability. In the related art, there are methods for preparing permeable bricks using tailings as raw materials, but these methods have problems such as low tailings utilization rate, unsatisfactory water permeability and mechanical properties. Summary of the invention
[0005] The invention provides a permeable brick and a preparation method thereof, so as to solve the problems of low tailings utilization rate, unsatisfactory permeability and mechanical properties in the existing method for preparing permeable bricks.
[0006] According to the first aspect of the present invention, the present invention provides a permeable brick, comprising the following raw materials in parts by weight: 75-85 parts of copper tailings with a particle size of 5-10 mesh, 15-25 parts of copper tailings with a particle size less than 200 mesh, and 14-16 parts of a binder.
[0007] In the above scheme, a permeable brick uses copper tailings as the main raw material and is prepared with a binder, which can realize the resource utilization of solid waste and improve economic benefits. Furthermore, the permeable brick of the present invention uses copper tailings with different coarse and fine particle sizes, so that the fine copper tailings can be bonded and coated on the surface of the coarse copper tailings by the binder, and the fine copper tailings are tightly combined with the coarse large particles. During the firing process, the coarse large particles and the fine powder are more adaptable to firing, and the formed sintered products adhere to the surface of the coarse aggregate, thereby forming interconnected pores between the coarse aggregates, thereby improving the permeability. The permeable brick of the present invention can improve the utilization rate of the copper tailings by limiting the copper tailings with a particle size of 5-10 mesh, the copper tailings with a particle size of less than 200 mesh, and the amount of the binder within a reasonable range, and at the same time, the components can play a good synergistic role, so that the prepared permeable brick has both high mechanical properties and high permeability coefficient.
[0008] Furthermore, the binder includes a PVA aqueous solution and magnesia clay.
[0009] In the above scheme, the binder includes PVA aqueous solution and magnesia clay. The PVA aqueous solution is a liquid binder. The PVA molecules contain a large number of hydroxyl groups, which can form hydrogen bonds with water molecules. During the preparation process, water is added to dissolve the PVA, and the hydroxyl groups form hydrogen bonds with the water molecules, so that the PVA molecules attract each other, and this interaction can be maintained after drying to form a strong bond. Magnesia clay has strong viscosity due to the combined effect of various factors such as inter-particle suction, adsorption, chemical reaction and moisture distribution. By selecting PVA aqueous solution and magnesia clay as binders, the synergistic effect between the two makes the binder have strong binding properties, which can reduce the amount of PVA and magnesia clay respectively, and the product has a certain green strength after molding. In addition, the addition of magnesia clay not only improves the green strength of the permeable brick, but also promotes the softening of the joints between the coarse and fine materials of the copper tailings during the high temperature stage of firing, thereby improving the mechanical properties of the permeable brick.
[0010] Furthermore, the binder is composed of 10 parts of PVA aqueous solution and 4-6 parts of magnesia clay.
[0011] In the above scheme, by controlling the amount of PVA aqueous solution and magnesia clay in the binder within a reasonable range, the permeable brick can maintain high mechanical properties and water permeability.
[0012] Furthermore, the mass concentration of the PVA aqueous solution is 1-3wt%.
[0013] By limiting the mass concentration of the PVA aqueous solution to a reasonable range, the adhesive can exert better bonding performance.
[0014] Furthermore, the green strength of the permeable brick after forming is greater than 1.5MPa; the compressive strength of the permeable brick is greater than 55MPa; the flexural strength of the permeable brick is greater than 6MPa; and the water permeability coefficient of the permeable brick is greater than 0.07cm / s.
[0015] According to a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned permeable brick, comprising the following steps:
[0016] Step (1): taking copper tailings, removing impurities, crushing and screening;
[0017] Step (2): taking raw materials according to weight: 75-85 parts of copper tailings with a particle size of 5-10 mesh, 15-25 parts of copper tailings with a particle size less than 200 mesh, and 14-16 parts of a binder;
[0018] Step (3): taking copper tailings with a particle size of 5-10 mesh, adding a portion of a binder, and mixing evenly to obtain a coarse material of copper tailings;
[0019] Step (4): taking copper tailings with a particle size less than 200 mesh, adding the remaining binder, and mixing evenly to obtain copper tailings fine material;
[0020] Step (5): adding the fine copper tailings in step (4) to the coarse copper tailings in step (3), mixing them evenly, and obtaining a mixture;
[0021] (6) aging, molding and drying the mixed material;
[0022] (7) The dried green body is fired to obtain a permeable brick.
[0023] In the above scheme, the preparation method of the present invention adopts the preparation scheme of copper tailings fine material wrapping copper tailings coarse material, so that the copper tailings fine material is bonded and coated on the surface of the copper tailings coarse material, and the copper tailings fine material is closely combined with the large-particle coarse material. During the sintering process, the sintering adaptability of the large-particle coarse material and the fine powder is enhanced, and the formed sintered product adheres to the surface of the coarse aggregate, thereby forming interconnected pores between the coarse materials, thereby improving the water permeability. The preparation method of the present invention is simple, low-cost, and easy to industrialize and mass-produce.
[0024] Furthermore, the binder used in step (3) includes a PVA aqueous solution.
[0025] Furthermore, the binder used in step (4) includes magnesia clay.
[0026] Furthermore, in step (6), the aging time is 12-36 hours; the molding pressure is 20-40 MPa; the drying temperature is 100-160° C., and the drying time is 2-4 hours.
[0027] In the above scheme, by controlling the aging time, molding pressure, drying temperature and time within a reasonable range, the mixture can be effectively aged, effectively molded and meet the requirements of appropriate drying, which is beneficial to subsequent firing.
[0028] Furthermore, in step (7), the firing temperature is 1100-1140° C. and the firing time is 80-90 min.
[0029] In the above scheme, the mechanical properties of the permeable bricks can be guaranteed by limiting the firing temperature and time within a reasonable range.
[0030] The technical solution provided by the present invention has the following beneficial effects:
[0031] The permeable brick of the present invention improves the utilization rate of copper tailings, realizes the resource utilization of solid waste, improves economic benefits, and has both high mechanical properties and high permeability coefficient.
[0032] The preparation method of the permeable brick of the present invention adopts a preparation scheme of copper tailings fine material wrapping copper tailings coarse material, so that the copper tailings fine material is bonded and coated on the surface of the copper tailings coarse material, the copper tailings fine material is closely combined with the large-particle coarse material, and the large-particle coarse material and fine powder are more adaptable to the sintering during the sintering process, and the formed sintered product adheres to the surface of the coarse aggregate, thereby forming interconnected pores between the coarse aggregates, thereby improving the water permeability. The preparation method of the present invention is simple, low in cost, and easy to industrialize and mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 This is a process flow chart for preparing permeable bricks according to Example 1 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the present invention, if the specific technology or conditions are not specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the instruments is not specified, they are all conventional products that can be purchased through regular channels. The raw materials used in the present invention can be easily purchased in the domestic market.
[0037] The chemical composition of the copper tailings in the embodiment is shown in Table 1 below:
[0038] Table 1
[0039]
[0040] The chemical composition of the magnesia clay in the embodiment is shown in Table 2 below:
[0041] Table 2
[0042]
[0043] The chemical composition of bentonite in the example is shown in Table 3 below:
[0044] Table 3
[0045]
[0046] In the examples, the particle size is characterized by the mesh number of the sieve, wherein the 5-10 mesh refers to the copper tailing particles that can all pass through the 5-mesh sieve but cannot pass through the 10-mesh sieve, and the less than 200 mesh refers to the copper tailing particles that can all pass through the 200-mesh sieve.
[0047] In the following examples and comparative examples, the test methods for the green strength, compressive strength, flexural strength and water permeability coefficient after molding are as follows:
[0048] 1. The test methods for the green strength after molding and the flexural strength of the product are all tested by the three-point bending method. The sample size is 10×10×60mm, the span is 20mm, and the loading rate is 0.5mm / min. Three groups of samples are taken for testing each time, and the average value is taken. The calculation formula is as follows.
[0049] R = 3PL / (2bh2)
[0050] Where R——flexural strength (MPa);
[0051] P——The load on the sample when it breaks (N);
[0052] L——span, i.e. the distance between the fulcrums (mm);
[0053] b——specimen width (mm);
[0054] h——Cross-sectional thickness of the specimen (mm)
[0055] 2. Test methods for compressive strength and water permeability coefficient: refer to JC / T 945-2005 permeable bricks for specific implementation.
[0056] Example 1
[0057] This embodiment provides a permeable brick, comprising the following raw materials by weight: 80 parts of copper tailings with a particle size of 5-10 mesh, 20 parts of copper tailings with a particle size less than 200 mesh, and 16 parts of a binder. The binder is composed of 10 parts of a 1wt% PVA aqueous solution and 6 parts of magnesia clay.
[0058] The preparation method of the permeable brick of this embodiment is as follows Figure 1 The process shown includes the following steps:
[0059] (1) Raw material pretreatment: Take the copper tailings, dry them in the sun and remove impurities, then crush, sieve and dry them.
[0060] (2) Take raw materials: 80g of copper tailings with a particle size of 5-10 mesh, 20g of copper tailings with a particle size less than 200 mesh, and a binder; the binder is composed of 10g of a 1.0wt% PVA aqueous solution and 6g of magnesia clay, and the magnesia clay is sieved through a 200-mesh sieve for later use.
[0061] (3) Take copper tailings with a particle size of 5-10 mesh, add PVA aqueous solution, and stir for 5-10 minutes until the mixture is evenly mixed to obtain treated copper tailings coarse material.
[0062] (4) Take copper tailings with a particle size of less than 200 mesh, add magnesia clay, and stir for 5-10 minutes until the mixture is evenly mixed to obtain copper tailings fine material.
[0063] (5) Add the fine copper tailings in (4) to the coarse copper tailings in (3), and stir for 5-10 minutes until the mixture is uniformly mixed to obtain a mixture.
[0064] (6) The mixture is aged in a closed environment for 48 hours, the aged mixture is formed in a vibrating brick machine at a standard pressure of 30 MPa, and then placed in an oven for drying at 100°C for 4 hours.
[0065] (7) The dried green body is fired at 1100°C for 90 minutes to obtain a permeable brick.
[0066] The green strength after molding is greater than 1.5MPa. After high-temperature firing, the permeable brick sample has a compressive strength of 62MPa, a flexural strength of 6.4MPa, and a permeability coefficient of 0.081cm / s.
[0067] Example 2
[0068] This embodiment provides a permeable brick comprising the following raw materials by weight: 75 parts of copper tailings with a particle size of 5-10 mesh, 25 parts of copper tailings with a particle size less than 200 mesh, and 14 parts of a binder. The binder is composed of 10 parts of a 3wt% PVA aqueous solution and 4 parts of magnesia clay.
[0069] The method for preparing the permeable brick of this embodiment comprises the following steps:
[0070] (1) Raw material pretreatment: Take the copper tailings, dry them in the sun and remove impurities, then crush, sieve and dry them.
[0071] (2) Take raw materials: 75g of copper tailings with a particle size of 5-10 mesh, 25g of copper tailings with a particle size less than 200 mesh, and a binder; the binder is composed of 10g of a 3.0wt% PVA aqueous solution and 4g of magnesia clay, and the magnesia clay is sieved through a 200-mesh sieve for later use.
[0072] (3) Take copper tailings with a particle size of 5-10 mesh, add PVA aqueous solution, and stir for 5-10 minutes until the mixture is uniform, so as to obtain treated copper tailings coarse material.
[0073] (4) Take copper tailings with a particle size of less than 200 mesh, add magnesia clay, and stir for 5-10 minutes until the mixture is evenly mixed to obtain copper tailings fine material.
[0074] (5) Add the fine copper tailings in 4) to the coarse copper tailings in 3), and stir for 5-10 minutes until the mixture is uniform, to obtain a mixture.
[0075] (6) The mixture is aged in a closed environment for 24 hours, the aged mixture is formed in a vibrating brick machine at a standard pressure of 30 MPa, and then placed in an oven for drying at 120 degrees Celsius for 3 hours.
[0076] (7) The dried green body is kept at 1120°C for 80 minutes and fired to obtain a permeable brick.
[0077] The green strength after molding is greater than 1.5MPa. After high-temperature firing, the permeable brick sample has a compressive strength of 66MPa, a flexural strength of 6.5MPa, and a permeability coefficient of 0.076cm / s.
[0078] Example 3
[0079] This embodiment provides a permeable brick comprising the following raw materials by weight: 85 parts of copper tailings with a particle size of 5-10 mesh, 15 parts of copper tailings with a particle size less than 200 mesh, and 15 parts of a binder. The binder is composed of 10 parts of a 2wt% PVA aqueous solution and 5 parts of magnesia clay.
[0080] The method for preparing the permeable brick of this embodiment comprises the following steps:
[0081] (1) Raw material pretreatment: Take the copper tailings, dry them in the sun and remove impurities, then crush, sieve and dry them.
[0082] (2) Take raw materials: 85g of copper tailings with a particle size of 5-10 mesh, 15g of copper tailings with a particle size less than 200 mesh, and a binder; the binder is composed of 10g of a 2.0wt% PVA aqueous solution and 5g of magnesia clay, and the magnesia clay is sieved through a 200-mesh sieve for later use.
[0083] (3) Take copper tailings with a particle size of 5-10 mesh, add PVA aqueous solution, and stir for 5-10 minutes until the mixture is uniform, so as to obtain treated copper tailings coarse material.
[0084] (4) Take copper tailings with a particle size of less than 200 mesh, add magnesia clay, and stir for 5-10 minutes until the mixture is evenly mixed to obtain copper tailings fine material.
[0085] (5) Add the fine copper tailings in 4) to the coarse copper tailings in 3), and stir for 5-10 minutes until the mixture is uniform, to obtain a mixture.
[0086] (6) The mixture is aged in a closed environment for 24 hours, the aged mixture is formed in a vibrating brick machine at a standard pressure of 30 MPa, and then placed in an oven for drying at 160 degrees Celsius for 2 hours.
[0087] (7) The dried green body is kept at 1140°C for 80 minutes and fired to obtain a permeable brick.
[0088] The green strength after molding is greater than 1.5MPa. After high-temperature firing, the permeable brick sample has a compressive strength of 58MPa, a flexural strength of 6.1MPa, and a permeability coefficient of 0.083cm / s.
[0089] Comparative Example 1
[0090] This comparative example provides a permeable brick, and the preparation method thereof comprises the following steps:
[0091] (1) Raw material pretreatment: Take the copper tailings, dry them in the sun and remove impurities, then crush, sieve and dry them.
[0092] (2) Take raw materials: 80g of copper tailings with a particle size of 5-10 mesh, 20g of copper tailings with a particle size less than 200 mesh, and a binder; the binder is composed of 10g of a 1.0wt% PVA aqueous solution and 6g of magnesia clay.
[0093] (3) Add copper tailings with a particle size of 5-10 mesh, copper tailings with a particle size of less than 200 mesh, PVA aqueous solution and magnesia clay into a container, and stir for 10-30 minutes until the mixture is uniform, to obtain a mixture.
[0094] (4) The mixture is aged in a closed environment for 48 hours, the aged mixture is formed in a vibrating brick machine at a standard pressure of 30 MPa, and then placed in an oven for drying at 100 degrees Celsius for 4 hours.
[0095] (5) The dried green body is kept at 1100°C for 90 minutes and fired to obtain a permeable brick.
[0096] The green strength after molding is greater than 1.5MPa. After high-temperature firing, the permeable brick sample has a compressive strength of 63MPa, a flexural strength of 5.6MPa, and a permeability coefficient of 0.026cm / s.
[0097] Comparative Example 2
[0098] This comparative example provides a permeable brick, and the preparation method thereof comprises the following steps:
[0099] (1) Raw material pretreatment: Take the copper tailings, dry them in the sun and remove impurities, then crush, sieve and dry them.
[0100] (2) Take raw materials: 80g of copper tailings with a particle size of 5-10 mesh, 20g of copper tailings with a particle size less than 200 mesh, and a binder; the binder is composed of 10g of a 1.0wt% PVA aqueous solution and 6g of magnesia clay.
[0101] (3) Add copper tailings with a particle size of 5-10 mesh, copper tailings with a particle size of less than 200 mesh, and magnesia clay into a ball mill for mixing, with a mass ratio of material: ball: water of 1:0.2:1, a rotation speed of 30 r / min, and mix for 0.5-2 h. After the slurry is dried, it is broken up with a high-speed powder mill to obtain a mixture.
[0102] (4) Take the mixture, add the PVA aqueous solution, stir for 5-10 minutes until the mixture is uniform, and age in a closed environment for 48 hours. After the aged mixture is formed in a vibrating brick machine at a standard pressure of 30 MPa, it is placed in an oven and dried at 100 degrees Celsius for 4 hours.
[0103] (5) The dried green body is kept at 1100°C for 90 minutes and fired to obtain a permeable brick.
[0104] The green strength after molding is greater than 1.5MPa. After high-temperature firing, the permeable brick sample has a compressive strength of 65MPa, a flexural strength of 6.8MPa, and a permeability coefficient of 0.022cm / s.
[0105] Comparative Example 3
[0106] This comparative example provides a permeable brick, and the preparation method thereof comprises the following steps:
[0107] (1) Raw material pretreatment: take copper tailings, dry them in the sun and remove impurities, and then crush, sieve and dry the copper tailings after impurities removal;
[0108] (2) Take raw materials: 70g of copper tailings with a particle size of 5-10 mesh, 30g of copper tailings with a particle size less than 200 mesh, and a binder; the binder is composed of 10g of a 1.0wt% PVA aqueous solution and 6g of magnesia clay;
[0109] (3) taking copper tailings with a particle size of 5-10 mesh, adding PVA aqueous solution, stirring for 5-10 minutes until the mixture is uniform, and obtaining treated copper tailings coarse material;
[0110] (4) taking copper tailings with a particle size of less than 200 mesh, adding magnesia clay, and stirring for 5-10 minutes until the mixture is uniform, thereby obtaining fine copper tailings;
[0111] (5) adding the fine copper tailings in (4) to the coarse copper tailings in (3), stirring for 5-10 minutes until the mixture is uniformly mixed to obtain a mixture;
[0112] (6) aging the mixture in a closed environment for 48 hours, forming the aged mixture in a vibrating brick machine at a standard pressure of 30 MPa, and drying it in an oven at 100 degrees Celsius for 4 hours;
[0113] (7) The dried green body is kept at 1100°C for 90 minutes and fired to obtain a permeable brick.
[0114] The green strength after molding is greater than 1.5MPa. After high-temperature firing, the permeable brick sample has a compressive strength of 63MPa, a flexural strength of 6.5MPa, and a permeability coefficient of 0.038cm / s.
[0115] Comparative Example 4
[0116] This comparative example provides a permeable brick, and the preparation method thereof comprises the following steps:
[0117] (1) Raw material pretreatment: take copper tailings, dry them in the sun and remove impurities, and then crush, sieve and dry the copper tailings after impurities removal;
[0118] (2) Take raw materials: 90g of copper tailings with a particle size of 5-10 mesh, 10g of copper tailings with a particle size less than 200 mesh, and a binder; the binder is composed of 10g of a 1.0wt% PVA aqueous solution and 6g of magnesia clay;
[0119] (3) taking copper tailings with a particle size of 5-10 mesh, adding PVA aqueous solution, stirring for 5-10 minutes until the mixture is uniform, and obtaining treated copper tailings coarse material;
[0120] (4) taking copper tailings with a particle size of less than 200 mesh, adding magnesia clay, and stirring for 5-10 minutes until the mixture is uniform, thereby obtaining fine copper tailings;
[0121] (5) adding the fine copper tailings in (4) to the coarse copper tailings in (3), stirring for 5-10 minutes until the mixture is uniformly mixed to obtain a mixture;
[0122] (6) aging the mixture in a closed environment for 48 hours, forming the aged mixture in a vibrating brick machine at a standard pressure of 30 MPa, and drying it in an oven at 100 degrees Celsius for 4 hours;
[0123] (7) The dried green body is kept at 1100°C for 90 minutes and fired to obtain a permeable brick.
[0124] The green strength after molding is greater than 1.5MPa. After high-temperature firing, the permeable brick sample has a compressive strength of 48MPa, a flexural strength of 5.2MPa, and a permeability coefficient of 0.086cm / s.
[0125] Comparative Example 5
[0126] This comparative example provides a permeable brick, and the preparation method thereof comprises the following steps:
[0127] (1) Raw material pretreatment: take copper tailings, dry them in the sun and remove impurities, and then crush, sieve and dry the copper tailings after impurities removal;
[0128] (2) taking raw materials: 80 g of copper tailings with a particle size of 5-10 mesh, 20 g of copper tailings with a particle size less than 200 mesh, and a binder; the binder is 10 g of a 5.0 wt% PVA aqueous solution;
[0129] (3) Take copper tailings with a particle size of 5-10 mesh, add PVA aqueous solution, and stir for 5-10 minutes until the mixture is uniform, so as to obtain treated copper tailings coarse material.
[0130] (4) adding the copper tailings with a particle size of less than 200 meshes into the copper tailings coarse material in (3), stirring for 5-10 minutes until the mixture is uniformly mixed to obtain a mixture.
[0131] (5) The mixture is aged in a closed environment for 48 hours, the aged mixture is formed in a vibrating brick machine at a standard pressure of 30 MPa, and then placed in an oven for drying at 100 degrees Celsius for 4 hours.
[0132] (6) The dried green body is kept at 1100°C for 90 minutes and fired to obtain a permeable brick.
[0133] The green strength after molding is less than 1.0MPa. After high-temperature firing, the permeable brick sample has a compressive strength of 41MPa, a flexural strength of 4.8MPa, and a permeability coefficient of 0.085cm / s.
[0134] Comparative Example 6
[0135] This comparative example provides a permeable brick, and the preparation method thereof comprises the following steps:
[0136] (1) Raw material pretreatment: take copper tailings, dry them in the sun and remove impurities, and then crush, sieve and dry the copper tailings after impurities removal;
[0137] (2) Take raw materials: 80g of copper tailings with a particle size of 5-10 mesh, 20g of copper tailings with a particle size less than 200 mesh, and a binder; the binder is 8g of magnesia clay;
[0138] (3) taking copper tailings with a particle size of 5-10 mesh, adding magnesia clay, and stirring for 5-10 minutes until the mixture is uniform, thereby obtaining a treated copper tailings coarse material;
[0139] (4) adding the copper tailings with a particle size of less than 200 mesh to the copper tailings coarse material in (3), stirring for 5-10 minutes until the mixture is uniform, to obtain a mixture;
[0140] (5) aging the mixture in a closed environment for 48 hours, forming the aged mixture in a vibrating brick machine at a standard pressure of 30 MPa, and drying it in an oven at 100 degrees Celsius for 4 hours;
[0141] (6) The dried green body is kept at 1100°C for 90 minutes and fired to obtain a permeable brick.
[0142] The green strength after molding is less than 1.0MPa. After high-temperature firing, the permeable brick sample has a compressive strength of 65MPa, a flexural strength of 6.7MPa, and a permeability coefficient of 0.032cm / s.
[0143] Comparative Example 7
[0144] This comparative example provides a permeable brick, and the preparation method thereof comprises the following steps:
[0145] (1) Raw material pretreatment: take copper tailings, dry them in the sun and remove impurities, and then crush, sieve and dry the copper tailings after impurities removal;
[0146] (2) taking raw materials: 80 g of copper tailings with a particle size of 5-10 mesh, 20 g of copper tailings with a particle size less than 200 mesh, and a binder; the binder is composed of 10 g of a 1.0 wt% PVA aqueous solution and 2 g of magnesia clay;
[0147] (3) taking copper tailings with a particle size of 5-10 mesh, adding PVA aqueous solution, stirring for 5-10 minutes until the mixture is uniform, and obtaining treated copper tailings coarse material;
[0148] (4) taking copper tailings with a particle size of less than 200 mesh, adding magnesia clay, and stirring for 5-10 minutes until the mixture is uniform, thereby obtaining fine copper tailings;
[0149] (5) adding the fine copper tailings in (4) to the coarse copper tailings in (3), stirring for 5-10 minutes until the mixture is uniformly mixed to obtain a mixture;
[0150] (6) aging the mixture in a closed environment for 48 hours, forming the aged mixture in a vibrating brick machine at a standard pressure of 30 MPa, and drying it in an oven at 100 degrees Celsius for 4 hours;
[0151] (7) The dried green body is kept at 1100°C for 90 minutes and fired to obtain a permeable brick.
[0152] The green strength after molding is less than 1.0MPa. After high-temperature firing, the permeable brick sample has a compressive strength of 45MPa, a flexural strength of 5.3MPa, and a permeability coefficient of 0.083cm / s.
[0153] Comparative Example 8
[0154] This comparative example provides a permeable brick, and the preparation method thereof comprises the following steps:
[0155] (1) Raw material pretreatment: take copper tailings, dry them in the sun and remove impurities, and then crush, sieve and dry the copper tailings after impurities removal;
[0156] (2) taking raw materials: 80 g of copper tailings with a particle size of 5-10 mesh, 20 g of copper tailings with a particle size less than 200 mesh, and a binder; the binder is composed of 10 g of a 1.0 wt% PVA aqueous solution and 6 g of bentonite;
[0157] (3) taking copper tailings with a particle size of 5-10 mesh, adding PVA aqueous solution, stirring for 5-10 minutes until the mixture is uniform, and obtaining treated copper tailings coarse material;
[0158] (4) taking copper tailings with a particle size of less than 200 mesh, adding bentonite, and stirring for 5-10 minutes until the mixture is uniform, thereby obtaining fine copper tailings;
[0159] (5) adding the fine copper tailings in (4) to the coarse copper tailings in (3), stirring for 5-10 minutes until the mixture is uniformly mixed to obtain a mixture;
[0160] (6) aging the mixture in a closed environment for 48 hours, forming the aged mixture in a vibrating brick machine at a standard pressure of 30 MPa, and drying it in an oven at 100 degrees Celsius for 4 hours;
[0161] (7) The dried green body is kept at 1100°C for 90 minutes and fired to obtain a permeable brick.
[0162] The green strength after molding is greater than 1.5MPa. After high-temperature firing, the permeable brick sample has a compressive strength of 56MPa, a flexural strength of 5.7MPa, and a permeability coefficient of 0.077cm / s.
[0163] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A permeable brick, characterized in that: The preparation method comprises the following raw materials in parts by weight: 75-85 parts of copper tailings with a particle size of 5-10 meshes, 15-25 parts of copper tailings with a particle size less than 200 meshes, and 14-16 parts of a binder; the binder is composed of 10 parts of a PVA aqueous solution and 4-6 parts of magnesia clay; the mass concentration of the PVA aqueous solution is 1-3wt%; The preparation method comprises the following steps: Step (1): taking copper tailings, removing impurities, crushing and screening; Step (2): taking raw materials according to weight: 75-85 parts of copper tailings with a particle size of 5-10 mesh, 15-25 parts of copper tailings with a particle size less than 200 mesh, and 14-16 parts of a binder; Step (3): taking copper tailings with a particle size of 5-10 mesh, adding PVA aqueous solution, and mixing evenly to obtain copper tailings coarse material; Step (4): taking copper tailings with a particle size of less than 200 mesh, adding magnesia clay, and mixing evenly to obtain copper tailings fine material; Step (5): adding the fine copper tailings in step (4) to the coarse copper tailings in step (3), mixing them evenly, and obtaining a mixture; (6) Aging, molding and drying the mixed material; (7) firing the dried green body to obtain a permeable brick; In step (7), the firing temperature is 1100-1140° C. and the firing time is 80-90 min.
2. The permeable brick according to claim 1, characterized in that: The green strength of the permeable brick after forming is greater than 1.5MPa; the compressive strength of the permeable brick is greater than 55MPa; the flexural strength of the permeable brick is greater than 6MPa; and the water permeability coefficient of the permeable brick is greater than 0.07 cm / s.
3. The method for preparing the permeable brick according to any one of claims 1 to 2, characterized in that: The steps include: Step (1): taking copper tailings, removing impurities, crushing and screening; Step (2): taking raw materials by weight: 75-85 parts of copper tailings with a particle size of 5-10 mesh, 15-25 parts of copper tailings with a particle size less than 200 mesh, and 14-16 parts of a binder; the binder is composed of 10 parts of a PVA aqueous solution and 4-6 parts of magnesia clay; the mass concentration of the PVA aqueous solution is 1-3wt%; Step (3): taking copper tailings with a particle size of 5-10 mesh, adding PVA aqueous solution, and mixing evenly to obtain copper tailings coarse material; Step (4): taking copper tailings with a particle size of less than 200 mesh, adding magnesia clay, and mixing evenly to obtain copper tailings fine material; Step (5): adding the fine copper tailings in step (4) to the coarse copper tailings in step (3), mixing them evenly, and obtaining a mixture; (6) Aging, molding and drying the mixed material; (7) firing the dried green body to obtain a permeable brick; In step (7), the firing temperature is 1100-1140° C. and the firing time is 80-90 min.
4. The preparation method according to claim 3, characterized in that: In step (6), the aging time is 12-36 hours; the molding pressure is 20-40 MPa; the drying temperature is 100-160°C, and the drying time is 2-4 hours.
Citation Information
Patent Citations
Sintered water-permeable brick produced by using smelting tailings, and preparation method thereof
CN108585788A
Method for preparing high-strength sintered water permeable brick from copper tailing sand
CN113683393A